Long live the Liver King: right-wing carnivorism and the digital dissemination of primal rhetoric - Muller, S. Marek; Rooney, David; Cerja, Cecilia (Frontiers in Communication, 2024)
In this study, we link pertinent concepts from rhetorical studies of the alt-right, animality studies, and conspiracism to explicate the production and dissemination of "carnivore diets'' through digital social networks. Taking the ideological and discursive interconnections of animality, hegemonic masculinity, and white nationalism seriously, we conceptualize primal rhetorical networks: a web of influencers and agitators who espouse an ahistorical, carnivorous primal rhetoric concerned with Modern Man's physical and spiritual downfall and his potential for resurrection by consuming nonhuman animals. We utilize a corpus of online texts and social media posts between 2020 and 2023 to perform an ideological rhetorical criticism of two interconnected, online Carnivore Diet gurus: the Liver King and the Raw Egg Nationalist. Drawing upon "conspiritual" tropes and raced/gendered depictions of nonhuman animal consumption, we demonstrate how these networked rhetors "sell" their lifestyles to make a profit and "convert" their followers into an ever-growing network of white nationalist, cisheterosexist, carnivorous ideologues.